Kajian Pola Sebaran Ruko yang Beralih Fungsi menjadi Kos-Kosan di Sekitar Kampus - Vania Dea Wibowo; Muhammar Khamdevi (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2019)
The purpose of this study was to determine the factors that caused the shophouse to switch to a boarding house for the potential elements of the UMN region, to know the pattern of distribution of functions of shophouses to boarding houses around the campus with a case study of boarding houses around UMN, and to find out the factors causing the distribution pattern of shop houses that switch functions to boarding houses with a case study of boarding houses around UMN. Nowadays, the spread of shop houses that change functions into boarding houses, especially around the center of activity. However, if the distribution of shophouses that change functions as a boarding house is not regulated so that it will cause the growth of wild function changes and spread to other areas causing disruption to regional land use. This study takes the title "Study of Distribution Patterns of Shophouse that Turns Function into Boarding Houses around Campus, Case Study: Shophouses around UMN Gading Serpong Campus." This research was conducted using descriptive qualitative research methods with case study research. Data collection for this study was carried out using observation, interviews, documentation, focus group discussions and also triangulation. Source of data used comes from primary data obtained directly from observations in the field and secondary data used as supplementary or comparative data. This research was conducted in March to July 2019 at a predetermined research location, namely a shop in an area with a radius of 800m from UMN. This research is focused by using the urban theories of Hamid Shirvani and Markus Zahn as a mapping tool to read the elements of the region to get results in the form of factors that cause the change of shophouse functions into a boarding house to the potential of the area, the pattern of distribution and changes in buildings (especially in terms of space and facade) shophouses that switch functions to boarding houses around the campus as centers of activity by using case study of boarding houses around UMN. The conclusion obtained contains the factors that the function of the shop-house change into a boarding house for the potential of the area, the distribution pattern of the boarding houses around UMN, as well as the distribution pattern factors.